Proceedings of the 5th Annual SIGCSE/SIGCUE ITiCSEconference on Innovation and Technology in Computer Science Education 2000
DOI: 10.1145/343048.343063
|View full text |Cite
|
Sign up to set email alerts
|

Does it help to have some programming experience before beginning a computing degree program?

Abstract: There is an intuitive perception that students with prior programming experience have an initial advantage in an introductory programming course, but that this advantage may decrease over the duration of the course if the style of programming is different from what the student has learnt previously. This paper reports on a study that indicates that students who have experience in at least one programming language at the beginning of an introductory programming course perform significantly better in the assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 4 publications
2
77
3
3
Order By: Relevance
“…Evans and Simkin (1989) noted that prior BASIC programming experience was a predictor for scores on the second exam in an introductory BASIC programming course. Hagan and Markham (2000) also examined the effect of prior programming experience on performance in an introductory Java programming course. They found that the students with prior programming experience did better on the first and last stages of the course project (the second stage was omitted from their analysis) as well as the first two exams and the overall course grade.…”
Section: Prior Programming Experiencementioning
confidence: 99%
“…Evans and Simkin (1989) noted that prior BASIC programming experience was a predictor for scores on the second exam in an introductory BASIC programming course. Hagan and Markham (2000) also examined the effect of prior programming experience on performance in an introductory Java programming course. They found that the students with prior programming experience did better on the first and last stages of the course project (the second stage was omitted from their analysis) as well as the first two exams and the overall course grade.…”
Section: Prior Programming Experiencementioning
confidence: 99%
“…Prior programming experience has been found to be useful for ICT students (Hagan & Markham, 2000;Kori et al, 2016), but the students who had learned ICT at a general education level did not find the knowledge to be useful at university. Students also had different goals for studying ICT at university, but only a few had sufficient information about the curriculum.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…On leitud, et varasema programmeerimiskogemusega üliõpilased saavutavad paremaid õpitulemusi (Hagan & Markham, 2000) ja hindavad õpinguid kõrgkoolis lihtsamaks kui varasema programmeerimiskogemuseta üliõpilased (Kori, Pedaste, Leijen, & Tõnisson, 2016). Seega võivad IKT-õpingud keeruliste programmeerimise ja matemaatika õppeainete tõttu pooleli jätta just need üliõpilased, kellel puuduvad programmeerimiskogemused.…”
Section: Ikt Erialade Spetsiifikaunclassified
“…Given the complex and rich syntax of Java, there is not time to cover all basic concepts during an introductory course; this was demonstrated by the lack of error handling above. In addition, programming courses at HS level should also inspire those students, who are interested in a future career as computer scientists; especially given that prior programming experience has been shown to have a positive impact on university CS studies (Hagan & Markham, 2000). HS is the place in which future university students receive their basic skills; should we not then concentrate on giving them a solid ground in algorithmic thinking and programming, instead of in programming languages and syntax?…”
Section: Discussionmentioning
confidence: 99%